Applications of Modified Starches 2018
DOI: 10.5772/intechopen.74362
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Starch Nanoparticles

Abstract: In recent years, the increasing interest in nanomaterials of natural origin has led to several studies in the area of nano-sized particles from natural polysaccharide polymers, such as cellulose, starch, and chitin. These nanomaterials are used especially as a reinforcement in a polymeric matrix to improve the mechanical and barrier properties of the materials. Starch is a sustainable, abundant biopolymer produced by many plants as a source of storage energy; the main uses of starch are as food and industrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…As a result, sample group 2 has the optimal amount of nanofiller percentage of glutinous rice flour-based impression material, which is 15% wt. Fillers with nano-sized and uniform morphology can support surface area increases that easily duplicate thin areas, resulting in good detail reproduction [3,[49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, sample group 2 has the optimal amount of nanofiller percentage of glutinous rice flour-based impression material, which is 15% wt. Fillers with nano-sized and uniform morphology can support surface area increases that easily duplicate thin areas, resulting in good detail reproduction [3,[49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…The nanoparticles produced by this process typically have a diameter of less than 100 nm. Furthermore, due to the huge number of OH groups on their surface, these nanoparticles contain nano-crystal aggregates, which become firmly connected by hydrogen bonding, resulting in rapid thermal deterioration [ 31 ]. Bashir and Haripriya [ 32 ] reported that the swelling capacity of gamma-radiated wholewheat starch samples with doses of 0.5, 1, 2.5, 5, and 10 kGy increased dramatically.…”
Section: The Classification Basis Of the Preparation Methods Of Starc...mentioning
confidence: 99%
“…Grafting is mainly used in electrical engineering, production of bioplastics, agriculture as well as in pharmacy. Gelling agent in the production of gum and processed cheese loaves, fat replacers/fat mimetic [64,65] The acid hydrolysis of starch is performed at temperatures below the gelatinization temperature and favors properties such as solubility, pasting viscosity, gelatinization enthalpy, and swelling power, whereas the effect on granular morphology differs among species, tissues, and degrees of hydrolysis. For instance, a slight hydrolysis reveals no significant morphological alteration, which presupposes that the starch has not been boiled [66].…”
Section: Physical Modifications Of Isolated Starchesmentioning
confidence: 99%